Serum levels of miR-126 and miR-223 and outcomes in chronic kidney disease patients - Fourdinier, Ophélie; Schepers, Eva; Metzinger-Le Meuth, Valérie; Glorieux, Griet; Liabeuf, Sophie; Verbeke, Francis; Vanholder, Raymond; Brigant, Benjamin; Pletinck, Anneleen; Diouf, Momar; Burtey, Stéphane; Choukroun, Gabriel; et al. (Springer Science and Business Media LLC, 2019)
Several microRNAs (miRNAs) have been linked to chronic kidney disease (CKD) mortality, cardiovascular (CV) complications and kidney disease progression. However, their association with clinical outcomes remains poorly evaluated. We used real-time qPCR to measure serum levels of miR-126 and miR-223 in a large cohort of 601 CKD patients (CKD stage G1 to G5 patients or on renal replacement therapy - CKD G5D) from Ghent University Hospital and 31 healthy controls. All-cause mortality and cardiovascular and renal events were registered as endpoints over a 6 year follow-up period. miR-126 levels were significantly lower from CKD stage G2 on, compared to controls. The serum levels of miR-223 were significantly lower from CKD stage G3B on. When considering overall mortality, patients with levels of either miR-126 or miR-223 below the median had a lower survival rate. Similar results were observed for CV and renal events. The observed link between the two miRNAs' seric levels and mortality, cardiovascular events or renal events in CKD appears to depend on eGFR. However, this does not preclude their potential role in the pathophysiology of CKD. In conclusion, CKD is associated with a decrease in circulating miR-223 and miR-126 levels.